PEER umbrella systematic review of systematic reviews: Management of osteoarthritis in primary care - Ton, Joey (Can Fam Physician, 2020)
OBJECTIVE: To determine how many patients with chronic osteoarthritis pain respond to various non-surgical treatments. DATA SOURCES: PubMed and the Cochrane Library. STUDY SELECTION: Published systematic reviews of randomized controlled trials (RCTs) that included meta-analysis of responder outcomes for at least 1 of the following interventions were included: acetaminophen, oral nonsteroidal anti-inflammatory drugs (NSAIDs), topical NSAIDs, serotonin-norepinephrine reuptake inhibitors (SNRIs), tricyclic antidepressants, cannabinoids, counseling, exercise, platelet-rich plasma, viscosupplementation, glucosamine, chondroitin, intra-articular corticosteroids, rubefacients, or opioids. SYNTHESIS: In total, 235 systematic reviews were included. Owing to limited reporting of responder meta-analyses, a post hoc decision was made to evaluate individual RCTs with responder analysis within the included systematic reviews. New meta-analyses were performed where possible. A total of 155 RCTs were included. Interventions that led to more patients attaining meaningful pain relief compared with control included exercise (risk ratio [RR] of 2.36; 95% CI 1.79 to 3.12), intra-articular corticosteroids (RR = 1.74; 95% CI 1.15 to 2.62), SNRIs (RR = 1.53; 95% CI 1.25 to 1.87), oral NSAIDs (RR = 1.44; 95% CI 1.36 to 1.52), glucosamine (RR = 1.33; 95% CI 1.02 to 1.74), topical NSAIDs (RR = 1.27; 95% CI 1.16 to 1.38), chondroitin (RR = 1.26; 95% CI 1.13 to 1.41), viscosupplementation (RR = 1.22; 95% CI 1.12 to 1.33), and opioids (RR = 1.16; 95% CI 1.02 to 1.32). Preplanned subgroup analysis demonstrated no effect with glucosamine, chondroitin, or viscosupplementation in studies that were only publicly funded. When trials longer than 4 weeks were analyzed, the benefits of opioids were not statistically significant. CONCLUSION: Interventions that provide meaningful relief for chronic osteoarthritis pain might include exercise, intra-articular corticosteroids, SNRIs, oral and topical NSAIDs, glucosamine, chondroitin, viscosupplementation, and opioids. However, funding of studies and length of treatment are important considerations in interpreting these data.